2010
DOI: 10.1111/j.1467-8624.2010.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Flexibility in Drawings of Bilingual Children

Abstract: A. Karmiloff-Smith's (1990) task of drawing a nonexistent object is considered to be a measure of cognitive flexibility. The notion of earlier emergence of cognitive flexibility in bilingual children motivated the current researchers to request 4- and 5-year-old English-Hebrew and Arabic-Hebrew bilingual children and their monolingual peers to draw a flower and a house that do not exist (N=80). Bilinguals exhibited a significantly higher rate of interrepresentational flexibility in their drawings (e.g., "a gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 38 publications
2
56
0
3
Order By: Relevance
“…In one study, Bialystok (2010) found a bilingual advantage in processing complex stimuli in tasks that require executive processing components for conflict resolution, including switching and updating, even when no inhibition appears to be involved. Additionally, other evidence has shown that these effects of bilingualism extend to working memory tasks (Morales, Calvo & Bialystok, 2013), and cognitive flexibility (Adi-Japha, Berberich-Artzi, & Libnawi, 2010). However, in the area of working memory, the bilingual advantage has not been consistently found.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, Bialystok (2010) found a bilingual advantage in processing complex stimuli in tasks that require executive processing components for conflict resolution, including switching and updating, even when no inhibition appears to be involved. Additionally, other evidence has shown that these effects of bilingualism extend to working memory tasks (Morales, Calvo & Bialystok, 2013), and cognitive flexibility (Adi-Japha, Berberich-Artzi, & Libnawi, 2010). However, in the area of working memory, the bilingual advantage has not been consistently found.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for superior non-verbal executive function and conflict resolution in bilingual children has been reported in a number of studies (e.g., Adi-Japha, Berberich-Artzi, & Libnawi, 2010; Poulin-Dubois, Blaye, Coutya, & Bialystok, 2011; Yang, Yang, & Lust, 2011). For example, Carlson and Meltzoff (2008) administered executive function tasks to children who were English monolinguals, English-Spanish bilinguals, or English-speaking children enrolled in a second-language immersion elementary school.…”
Section: Bilingualism and Executive Functioningmentioning
confidence: 94%
“…Bilingual children in preschool produced more cross-category insertions to drawings when instructed to ''draw a flower that doesn't exist'' (Adi-Japha et al, 2010). In other words, bilingual children were more likely to draw components on their flower unrelated to a flower, such as a body part or clothes, whereas monolingual children were more likely to omit or add components related to a flower, such as drawing multiple stems or no petals (Adi-Japha et al, 2010).…”
Section: Inhibitory Controlmentioning
confidence: 99%